EFFECT OF FOREIGN FINANCE ON SME’S PRODUCTIVITYIN LAGOS, NIGERIA - Ekeocha, Hector Onyekachi; Olurin, Enitan Olurotimi; Akinyomi, John Oladele (Veredas do Direito, 2026)
This study explored the effect of foreign finance on the productivity of SMEs in Lagos State Nigeria. Adopting Pecking Order Theory and the Resource-Based Theory, the study hypothesised links between foreign finance and SMEs performance variable. The study employed a survey design using random sampling technique with 361 sample size out of a population of 5,344. Primary data were collected with the aid of a questionnaire on a five-point Likert scale distributed through hard and electronic means to SMEs in Lagos State. Both descriptive and inferential statistics with regression analysis were employed to examine the five hypotheses with the aid of Statistical Package for Social Sciences. The overall findings revealed that foreign finance elements of foreign direct investment (FDI), foreign venture capital (FVC), foreign loan (FL) and foreign grant (FG) had significant positive effect on the performance of SMEs in Lagos Statewith foreign grant leading the park. Size of the firm has no significant effect on SMEs performance. The study concluded that change foreign finance elements have significant effects on SMEs productivity in Lagos State. SMEs can draw insight from this study to engage in structuring their business to attract foreign investors. It is recommended that SMEs should make themselves attractive to foreign investors and grantors by structuring their companies and improve on their reporting process.